Does the development of the digital economy improve carbon emission efficiency? - Han, Jun; Jiang, Tianhe (Frontiers in Ecology and Evolution, 2022)
The improvement of carbon emissions efficiency is guided by high-quality economic development, and the organic integration of ecology and economy is an important goal of putting sustainable economic development into action. Based on China's provincial panel data from 2008 to 2019, this paper constructs a digital economy development index from the perspective of the digital economy, and analyzes its impacts on carbon emissions efficiency. The conclusion is that the development of the digital economy has significantly improved carbon emissions efficiency. Through the analysis of the spatial spillover effect, it is found that regional carbon emissions efficiency has a spatial correlation, but the development of the digital economy has no significant impact on the carbon emissions efficiency of neighboring regions. Industrial structure adjustment, the energy structure and technological progress are further analyzed as three mechanisms affecting carbon emissions efficiency. It is found that the quality of industrial structure adjustment significantly promotes the improvement of carbon emissions efficiency, the energy structure significantly inhibits its improvement, while the range of industrial structure adjustment and technological progress have no significant impact on carbon emissions efficiency. Based on the threshold effect, it is found that only when the energy structure is in the interval unit (0.1288, 0.2441) and technological progress is greater than 1.0591 can carbon emissions efficiency be promoted. Based on the above conclusions, we put forward corresponding policy suggestions.